Synchronized Reagent Delivery in Double Emulsions for Triggering Chemical Reactions and Gene Expression. Issue 8 (25th June 2021) - Stucki, Ariane; Jusková, Petra; Nuti, Nicola; Schmitt, Steven; Dittrich, Petra S.
Abstract: Microfluidic methods for the formation of single and double emulsion (DE) droplets allow for the encapsulation and isolation of reactants inside nanoliter compartments. Such methods have greatly enhanced the toolbox for high‐throughput screening for cell or enzyme engineering and drug discovery. However, remaining challenges in the supply of reagents into these enclosed compartments limit the applicability of droplet microfluidics. Here, a strategy is introduced for on‐demand delivery of reactants in DEs. Lipid vesicles are used as reactant carriers, which are co‐encapsulated in double emulsions and release their cargo upon addition of an external trigger, here the anionic surfactant sodium dodecyl sulfate (SDS). The reagent present inside the lipid vesicles stays isolated from the remaining content of the DE vessel until SDS enters the DE lumen and solubilizes the vesicles' lipid bilayer. The versatility of the method is demonstrated with two critical applications chosen as representative assays for high‐throughput screening: the induction of gene expression in bacteria and the initiation of an enzymatic reaction. This method not only allows for the release of the lipid vesicle content inside DEs to be synchronized for all DEs but also for the release to be triggered at any desired time. Abstract : Here, a reagent delivery system is introduced based on liposomes encapsulated in double emulsions, which is compatible with flow cytometry and microscopy analysis. The possibility of delaying and controlling reagent delivery in current high‐throughput compartmentalization systems is significantly extending their range of applications and further improves their compatibility with biological systems.